Associations of healthy eating index 2020 and its components with non-alcoholic fatty liver disease in type 2 diabetes patients and the mediating roles of metabolic indicators: NHANES 2007–2018 - Chen, Jingxiong; Diao, Haizhou; Zhang, Yuling; Hu, Ben; Qian, Kai; Zhang, Kaiguang; Zhang, Tengyue; Song, Jizhong (Frontiers in Nutrition, 2025)
BackgroundNon-alcoholic fatty liver disease (NAFLD) represents a major public health issue, especially among individuals diagnosed with Type 2 diabetes mellitus (T2DM), where its prevalence can reach up to 70%. This research examines the relationship between the Healthy Eating Index 2020 (HEI-2020) and its individual components with the occurrence of NAFLD in T2DM patients, while also investigating the potential mediating effects of various metabolic indicators.MethodsData from the National Health and Nutrition Examination Survey (NHANES) spanning 2007 to 2018 were utilized. This cross-section study included 1,770 T2DM patients, who were divided into NAFLD and non-NAFLD groups using the Fatty Liver Index as a diagnostic tool. The HEI-2020, which assesses diet quality, was computed based on 24-h dietary recall data. Key metabolic indicators such as the triglyceride-glucose (TyG) index, metabolic score (MS), mean arterial pressure, uric acid levels, and total cholesterol were evaluated.ResultsThe findings indicated that higher HEI-2020 scores were associated with a lower likelihood of NAFLD (odds ratio 0.978, 95% confidence interval: 0.959–0.998), with the strongest inverse associations observed in the top quartiles of diet quality. Whole fruits, greens and beans, and saturated fat were crucial dietary factors. Mediation analysis demonstrated that the TyG index and MS accounted for 5.11 and 36.94% of the relationship between HEI-2020 and NAFLD, respectively.ConclusionGreater adherence to the HEI-2020 is associated with a lower likelihood of NAFLD in T2DM patients, with metabolic indicators partially mediating this association. Enhancing diet quality, particularly by increasing the consumption of whole fruits and greens while reducing saturated fat intake, may be important in managing metabolic health and liver function in this vulnerable population.